MENUMBUHKAN CINTA BAHASA ARAB DENGAN BI’AH ‘ARABIYYAH DI PONDOK PESANTREN - Habibah, Aizzatin; Syihabuddin, Syihabuddin; Nurbayan, Yayan (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This research is a description of the programs implemented in the Assalafi Al Fithrah Islamic Boarding School in shaping an Arabic language environment (bī'ah 'Arabiyyah) and their planning. This description aims to describe the programs that are carried out and the planning for implementing these activities. The research method used is descriptive qualitative. The research data was collected through observation, interviews, and documentation. After the data is collected, it is analyzed by means of data display, data reduction, and verification or conclusion. The research results obtained are that there are 12 programs divided into four types, namely daily programs, weekly programs, monthly programs, and annual programs. To run these programs is equipped with planning, which includes the completeness of planning tools, planning components, vision and mission of the institution, curriculum, and program plans. However, there are obstacles that arise from the management of the pesantren, in which there is no written mandatory guideline regarding the formation of program planning. So, they still use the ATM (observe, imitate, and modify) system in evaluating each program to make it better for the next.